Family History and Risk of Recurrent Stroke. Issue 8 (August 2016) - Chung, Jong-Won; Kim, Beom Joon; Han, Moon-Ku; Kang, Kyusik; Park, Jong-Moo; Park, Sang-Soon; Park, Tai Hwan; Cho, Yong-Jin; Hong, Keun-Sik; Lee, Kyung Bok; Kim, Jae Guk; Ko, Youngchai; et al.
Abstract : Background and Purpose—: The association between family history of stroke and stroke recurrence remains unclear. Methods—: Using a web-based multicenter stroke registry database, information on history of stroke in first-degree relatives was collected prospectively for acute ischemic stroke patients who were hospitalized within 7 days of onset. The collected information was categorized as follows: type of the affected relative(s) with stroke (paternal, maternal, sibling, or 2 or more) and age of the relative's stroke onset (<50, 50–59, 60–69, and ≥70 years). Stroke recurrence was captured prospectively using a predetermined protocol. Subgroup analyses were performed according to the patient's age at the index stroke. Results—: Among 7642 patients, 937 (12.3%) had a history of stroke in their first-degree relatives and 475 (6.2%: 201 within and 274 after 3 weeks from index stroke) experienced stroke recurrence (median follow-up, 365 days). In multivariable Cox proportional hazard models, overall family history was not associated with stroke recurrence (hazard ratio, 1.08; 95% confidence interval, 0.81–1.43). However, the details of their family histories, including relative's age at stroke onset (<50 years: hazard ratio, 2.14; 95% confidence interval, 1.004–4.54) and stroke history in a sibling (hazard ratio, 1.67; 95% confidence interval, 1.09–2.58), were independently associated with stroke recurrence after adjusting for potential confounders. The associations appeared to be stronger in young adults with stroke (age, <55 years) than in older stroke patients. Conclusions—: This study suggests that elevated risks of recurrent stroke are associated with having relatives with early-onset stroke and siblings with stroke histories, implying that additional precautions may be needed in such populations. Abstract : Supplemental Digital Content is available in the text.